Directive illocutionary acts ‘suggest’ and its translation found in the novel new moon - Agustawan, Dewa Made (Linguistics and Culture Review, 2021)
The aim of this research is to determine the translation procedures of directive illocutionary acts ‘order’ found in the novel New Moon translated into Indonesian. The method in collecting the data using several steps, such as: note-taking, identifying the data, arranging the data, and classifying the data in the form of a table. The analysis uses the theory of translation procedures proposed by Vinay and Darbelnet in Venuti (2000) and the theory of directive illocutionary acts that are proposed by Searle (1969). The finding of the research is that there is directive illocutionary acts ‘suggest’ found in the novel “New Moon.” Secondly, the types of translation procedures that are found in the novel are only two out of seven procedures obtained from the novel namely; literal translation, and transposition.